2010 - Milcom 2010 Military Communications Conference 2010
DOI: 10.1109/milcom.2010.5680485
|View full text |Cite
|
Sign up to set email alerts
|

Tradeoff between reliability and security in block ciphering systems with physical channel errors

Abstract: In this paper, we study the effects of channel errors on security and decoding error probability of three encryption systems where encrypted message is sent and eavesdropped over binary symmetric channels (BSC). The three systems are all based on Data Encryption Standard (DES) in cipher feedback (CFB) mode. They are DES only (DC), DES concatenated with Reed Solomon encoding (DCRS), and DES concatenated with RS coding and S-box diffusion (DCRSS). We adopt linear cryptanalysis to quantitatively measure the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…channel has four different states out of which states S 0 and S 2 behave like BSC channels, where in state S 0 , channel behaves like an error free BSC with capacity C(S 1 ) = 1, and in state S 2 , it acts like a BSC with cross over probability of α and capacity of C(S 2 ) = 1 − h(α), where h is binary entropy. However, for S 1 and S 3 , we need to compute the mutual information of input-output vectors given the current state based on their transition probabilities in (1) and (2). For S 1 we have…”
Section: Alice-bob Channel Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…channel has four different states out of which states S 0 and S 2 behave like BSC channels, where in state S 0 , channel behaves like an error free BSC with capacity C(S 1 ) = 1, and in state S 2 , it acts like a BSC with cross over probability of α and capacity of C(S 2 ) = 1 − h(α), where h is binary entropy. However, for S 1 and S 3 , we need to compute the mutual information of input-output vectors given the current state based on their transition probabilities in (1) and (2). For S 1 we have…”
Section: Alice-bob Channel Modelingmentioning
confidence: 99%
“…There have been a few studies on how channel error affects reliability of the message received by Bob [1]. However, very few analytical works focused on the impact of channel noise on system secrecy, as well as Eve's performance [2].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the IP encountered at the eavesdropper is used to evaluate the security performance, while the reliability performance is measured by the OP experienced at the destination. In [23], the authors studied the employment of various block cipher encryption algorithms from the perspective of both reliability and security and showed that there exists a tradeoff between communication reliability and security. Later on, the authors of [24] investigated the SRT for the downlink cloud radio access networks and the channel estimation errors were considered and the impact of the times of training on the security and reliability performance was also analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Security and reliability are two vital indexes of communication systems, but they fail to have good performance simultaneously in many cases. Therefore, it is of great significance to enhance the security-reliability trade-off (SRT) [7] performance based on the CR network.…”
Section: Introductionmentioning
confidence: 99%